Chigutisaurid amphibians from the Upper Triassic of Argentina and their Phylogenetic relationships - Marsicano, Claudia Alicia (2000)
A revision of the temnospondyl chigutisaurids from the Upper Triassic of Argentina is presented. The validity of the taxa originally proposed is discussed in the light of new material. The genus Pelorocephalus (Chigutisauridae) is diagnosed by the presence of a longitudinally keeled cultriform process, occurrence of the anterior Meckelian fenestra on the suture between splenial and postsplenial, location of the chordatympanic foramen on the contact between angular and prearticular, and exposure of the angular on the lingual mandibular surface. Three species, Pelorocephalus mendozensis, P. tenax and P. cacheutensis, are distinguished mainly by differences in the structure of the occiput. Phylogenetic relationships among all known representatives of this family, including taxa from India and Australia, are discussed.